The Gambia : Request for a Three-Year Arrangement Under the Extended Credit Facility: Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2012)
This paper discusses the request from Gambian authorities for a three-year arrangement under the extended credit facility (ECF). The Gambian economy performed well during the previous IMF arrangement, which expired at the end of March 2011; however, there were slippages under the program. The authorities requested a new three-year ECF arrangement, with a large initial disbursement, but relatively low access overall. The initial disbursement would support stability during the current drought crisis, while remaining disbursements would encourage fiscal adjustment and catalyze donor support for the poverty reduction strategy.